Effect of Strength Training on Plasma Levels of Homocysteine in Patients with Type 2 Diabetes - Silva, Alexandre de Souza e (Int J Prev Med, 2019)
BACKGROUND: The objective of this study was to analyze the effects of strength training on plasma homocysteine levels and cardiovascular risk factors in patients with type 2 diabetes. METHODS: The sample consisted of 14 diabetic women with a mean age of 68 ± 6 years. Biochemical evaluations and anthropometric measurements were taken before and after training. Training sessions lasted 50 min and comprised three sets of 8–12 repetitions each. The established load was 60% of 1 repetition maximum. RESULTS: After the training program, it was observed that the levels of homocysteine (average before 13.4 ± 2.9 and after 12.8 ± 3.3, P = 0.40), very low-density lipoprotein (LDL) (average before 41.9 ± 17.0 and after 36.2 ± 11.8, P = 0.47), total cholesterol (average before 214.4 ± 60.6 and after 190.2 ± 62.3, P = 0.09), triglycerides (average before 209.3 ± 85.4 and after 181.5 ± 59.2, P = 0.47), and blood glucose (average before 123.5 ± 30.4 and after 110.1 ± 24.7, P = 0.26) showed no significant changes, but the LDL (average before 129.1 ± 63.4 and after 95.7 ± 53.3, P = 0.04), high-density lipoprotein (average before 43.2 ± 12.0 and after 58.2 ± 15.6, P = 0.01), lean mass (average before 41.1 ± 5.7 and after 42.8 ± 5.4, P = 0.008), fat mass (average before 31.4 ± 8.8 and after 29.7 ± 8.5, P = 0.001), and percentage fat (average before 42.6 ± 4.0 and after 40.3 ± 4.6, P = 0.000) showed significant changes. CONCLUSIONS: This study concluded that strength training does not improve homocysteine levels, but help to improve the lipoprotein profile in type 2 diabetic patients.